Impact Employee Performance Through the Role of Compensation, Motivation and Dicipline at PT. Antarmitra Sembada Batam - Windayati, Diana; Auzar, Silvia Revana; Pratama, Muhammad Guntur (Universitas Batam, 2023)
In the era of globalization and modernization, corporate competition is getting sharper, human resources need to consistenly engage in proactive self-development and swiftly adapt to changing times. Every company must improve employee performance in order to continue to persist in business, special case at pharmaceutical sector. Of course, improving employee performance is important for them . The aim of this research was to determine and analyze the impact of compensation, work motivation, and work discipline on employee performance at PT. Antermitra Sembada Batam. The research methode using quantitative method. Employees of PT. Antermitra Sembada Batam Branch as population with a total of 55 (2022), sample is 55 respondents. The primary method of data collection involved distributing questionnaires to the participants. Analysis of the gathered data was performed utilizing multiple linear regression analysis within a quantitative research framework, processing using the SPSS version 23 software program. The results of research indicate that compensation, has insignificant impact on the employees performance with a probability value of 0.134 > 0.05. Both of motivation and dicipline has a significant impact on the employees performance with a probability value of 0.035 < 0.05; 0.011 < 0.05. The coefficient of determination value of 35.6% could be attribute of compensation, work motivation, and work discipline and the majority, accounnting 64.4% , attribute by another variables not explore.